Implementasi Manajemen Lembaga Pendidikan Islam Muhammadiyah di Indonesia - Sugiran Sugiran (Departement of Mathematics Education, 2023)
The point of this examination is to look at in more profundity the execution of the board of Muhammadiyah Islamic instructive foundations in Indonesia. This examination was composed in light of writing audit and top to bottom comprehension and collected understanding from different believed essential book sources. This kind of examination is subjective with a library research approach. Information assortment procedures are completed utilizing documentation. Information sources come from books and diaries. The information examination procedure utilizes content investigation. The aftereffects of the examination show that as an Islamic association, Muhammadiyah is reliably dedicated to propelling the country's life through the schooling system. Since its foundation Muhammadiyah instructive organizations have proceeded to create and work on both in amount and quality, however there are additionally establishments that have encountered difficulties and even been shut. This is the dynamic of instructive organizations that should be acknowledged. Up until this point, the administration utilized by Muhammadiyah has made the organizers behind Muhammadiyah schools excited about rivalry. Be that as it may, as per the creator, the ongoing administration should be entirely assessed to work on the nature of Muhammadiyah instruction all in all.